IMPACT CREATIVE TRENDS KHARKIV ARCHITECTURAL SCHOOL ON CONTEMPORARY URBAN ENVIRONMENT - , Я. В. (Municipal economy of cities. Series: «Economy science», 2013)
The problems of the formation of the Kharkov school of architecture of the late XIX - the middle of the twentieth century. Analyzes the impact of lessons learned on development of the modern architecture of the city.